1995
DOI: 10.1111/j.1600-051x.1995.tb01800.x
|View full text |Cite
|
Sign up to set email alerts
|

Periodontal healing and periopathogenic microflora in smokers and non‐smokers

Abstract: The aim of the present study was to monitor the clinical and microbiological effects of non-surgical therapy in smokers and non-smokers. The subject material included 32 patients (age range 32-61 years), 11 men and 21 women with moderate to severe periodontitis. 17 patients were smokers ( > or = 15 cigarettes/day) and 15 non-smokers. All patients were subjected to non-surgical periodontal therapy performed by a dental hygienist. Periodontal variables (plaque index, gingival index and probing depth) were regist… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

8
100
5
4

Year Published

1999
1999
2022
2022

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 123 publications
(117 citation statements)
references
References 44 publications
8
100
5
4
Order By: Relevance
“…Bergström and Preber 4) suggested that inflammatory gingival response to plaque accumulation, such as bleeding, redness and exudation, is suppressed by cigarette smoking. Periodontal healing function is poor in smokers 9,14) . This may have affected the amount of time required for improvement in gingival recession.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Bergström and Preber 4) suggested that inflammatory gingival response to plaque accumulation, such as bleeding, redness and exudation, is suppressed by cigarette smoking. Periodontal healing function is poor in smokers 9,14) . This may have affected the amount of time required for improvement in gingival recession.…”
Section: Discussionmentioning
confidence: 99%
“…Nonsurgical approaches to treating gingival recession of interdental papillae include correction of traumatic oral hygiene methods, restorative treatment, the orthodontic approach and repeated curettage of the papilla 13) . To the best of our knowledge, however, only a few reports have shown recovery of the interdental papillae by a nonsurgical method, and in those cases the recovery occurred during initial periodontal therapy 17) and without periodic curettage 14,18) . In terms of recession on the labial surface, several reports have demonstrated successful root coverage resulting from non-surgical therapy [1][2][3]12,13,15) .…”
Section: Introductionmentioning
confidence: 99%
“…With regards to the subgingival plaque microbiota, A. actinomycetemcomitans and P gingivalis were almost totally eradicated and P intermedius was reduced to about 30% in both groups (55). A study by Grossi et al in 1997 (59) showed that current smokers have less healing and reduction in subgingival Bacteroids forsythus and POlphyromonas gingivalis after treatment compared to former and non-smokers, suggesting that smoking impair periodontal healing.…”
Section: Smoking and Its Effects On Periodontal Healingmentioning
confidence: 96%
“…The influence of smoking on the short-term outcome of non-surgical therapy clinically as well as microbiologically was evaluated (55). The clinical results showed a statistically significant reduction of pocket depth and number of diseased sites in both smokers and nonsmokers patients.…”
Section: Smoking and Its Effects On Periodontal Healingmentioning
confidence: 99%
“…A meta-analysis by Labriola et al (2005) evaluated the impact of smoking on non-surgical periodontal therapy and reported that probing depth reduction in sites where probing depth was initially equal to or more than 5 mm was significantly greater in non-smokers than in smokers in eight studies (Grossi et al 1997, Mongardini et al 1999, Palmer et al 1999, Preber et al 1995, Pucher et al 1997, Renvert et al 1998, Ryder et al 1999, Williams et al 2001.…”
Section: Introductionmentioning
confidence: 99%